Hereditary Retinopathies Progress in Development of Genetic and Molecular Therapies - Humphries, Pete. (SpringerBriefs in Genetics,, 2012)
The hereditary retinopathy, retinitis pigmentosa (RP), which affects 1 in 3,500 people worldwide, is the most common cause of registered visual handicap among those of the working age in developed countries. RP is a highly variable disorder where patients may develop symptomatic visual loss in early childhood, while others may remain asymptomatic until mid-adulthood. Most cases of RP segregate in autosomal dominant, recessive or X-linked recessive modes, with approximately 41 genes being implicated in disease pathology to date (RetNet). The extensive genetic heterogeneity associated with autosomal dominant RP (adRP) is an undisputed hindrance to the development of genetically based therapeutics.